Mitochondrial ROS and involvement of Bcl-2 as a mitochondrial ROS regulator - Chong, S.; Low, I.; Pervaiz, Shazib (Elsevier, 2014)
Mitochondria are the major intracellular source of reactive oxygen species (ROS). While excessive mitochondrial ROS (mitoROS) production induces cell injury and death, there is accumulating evidence that non-toxic low levels of mitoROS could serve as important signaling molecules. Therefore, maintenance of mitoROS at physiological levels is crucial for cell homeostasis as well as for survival and proliferation. This review describes the various mechanisms that keep mitoROS in check, with particular focus on the role of the onco-protein Bcl-2 in redox regulation. In addition to its canonical anti-apoptotic activity, Bcl-2 has been implicated in mitoROS regulation by its effect on mitochondrial complex IV activity, facilitating the mitochondrial incorporation of GSH and interaction with the small GTPase-Rac1 at the mitochondria. We also discuss some of the plausible mechanism(s) which allows Bcl-2 to sense and respond to the fluctuations in mitoROS.